Descemet Stripping Endothelial Keratoplasty for Fuchs' Endothelial Corneal Dystrophy: Five-Year Results of a Prospective Study - Wacker, Katrin; Baratz, Keith H; Maguire, Leo J; McLaren, Jay W; Patel, Sanjay V (Ophthalmology (Rochester, Minn.), 2016)
To determine 5-year outcomes of Descemet stripping endothelial keratoplasty (DSEK) for Fuchs' endothelial corneal dystrophy (FECD). Prospective cohort study. Fifty-two eyes of 45 subjects with FECD undergoing primary DSEK. Subjects were examined before and at fixed intervals through 60 months after DSEK. At each visit, graft survival was determined by slit-lamp examination; best spectacle-corrected visual acuity (BSCVA) was measured using the electronic Early Treatment Diabetic Retinopathy Study (ETDRS) protocol; total anterior corneal higher-order aberrations (HOAs) were derived from corneal topography; and corneal backscatter, corneal thickness, and endothelial cell density were measured from confocal microscopy images. Corneal thickness also was measured by ultrasonic pachymetry. Changes after DSEK were analyzed using generalized estimating equation models. Best-corrected visual acuity, HOAs, endothelial cell loss, corneal thickness, and corneal backscatter. Complete 60-month follow-up was possible in 34 eyes. Mean BSCVA±standard deviation improved from 0.45±0.19 logarithm of the minimum angle of resolution (logMAR) (Snellen equivalent, 20/56) before DSEK to 0.09±0.13 logMAR (Snellen equivalent, 20/25) at 5 years (P < 0.001). Between 1 and 5 years, BSCVA improved by 0.06 logMAR (or 3 ETDRS letters; 95% confidence interval, 0.05-0.07 logMAR) per year (P < 0.001), and 56% of eyes were 0.1 logMAR (20/25) or better at 5 years. Graft thickness (approximately 155 μm) and corneal thickness (approximately 700 μm) did not change after surgery. Anterior corneal HOAs and backscatter decreased between 1 and 5 years (P ≤ 0.002). Six grafts failed, of which 4 were primary (iatrogenic); mean endothelial cell loss±standard deviation was 55±15% at 5 years. Between 1 and 5 years after DSEK, BSCVA continues to improve such that at 5 years, more than half of eyes see better than 20/25 with a mean total corneal thickness of 700 μm. Improvement in vision is accompanied by continued reduction in corneal haze and aberrations, suggesting ongoing remodeling of the cornea after restoration of endothelial function.